Elusive tipping point : China-India ties for a new order - Suryanarayana, P S (Chennai World Scientific, 2021)
The elusive tipping point: India-China ties for a new order is a timely foreign-policy-relevant book. This insightful book delves deep into the reasons for frequent diplomatic and strategic crises between Asia$1 (Bs two dynamic ancient civilisations with post modern capabilities. Set in the context of seventieth anniversary of china-india diplomacy, the spotlight is turned on their complex search for neighbourliness and global good. Often a mirage, the positive tipping point in their state-to-state relations is traced through the past, the present and the potential future. A controversial missed opportunity in the past and a collective-win approach for the present are explored. For Beijing and Delhi, imaginative all-weather dialogue is the best option if they wish to stabilise their engagement for the uncertain future. Despite their major military crisis, PRC and India are expected to shape a realistic post-covid world order.s
Keywords: Diplomatic relations